Do Critically Ill Patients Undergoing Continuous Renal Replacement Therapy Require Ceftaroline Dosage Adjustments? Ceftaroline PopPK Model and Dosage Simulations with the Probability of Target Attainment Analysis Based on Retrospective Data - Arkadiusz Adamiszak; Krzysztof Pietrzkiewicz; Alicja Bartkowska-Śniatkowska; Piotr Smuszkiewicz; Krzysztof Kusza; Edmund Grześkowiak; Agnieszka Bienert (Antibiotics)
Objectives: We aimed to develop a population pharmacokinetic (PopPK) model and evaluate dosing regimens for different renal clearances and continuous renal replacement therapy (CRRT) settings. Methods: Data were collected from four studies in intensive care unit (ICU) adult patients receiving 400–600 mg of ceftaroline every 8–12 h in a one-hour infusion. The PopPK model was developed according to non-linear mixed effects modeling implemented in Monolix 2024R1. To investigate dosing recommendations, Monte Carlo simulations and probability of target attainment (PTA) analysis were performed in Simulx 2024R1. Results: We collected 296 plasma concentrations from 29 non-CRRT patients and 24 pre-filter (systemic), 23 post-filter, and 23 effluent concentrations from four CRRT patients using WebPlotDigitizer (Version 4.7). A five-compartment model, with the first-order elimination from the central compartment and additional elimination with the effluent during CRRT, best described the ceftaroline concentrations. Creatinine clearance (ClCr) was identified as a covariate on the clearance of elimination (Cl) and CRRT modality on the central and peripheral compartments’ volumes and intercompartmental clearance. The results of dosage simulations for different CRRT modalities and ClCr, S. pneumoniae (MIC = 0.25 mg/L) and methicillin-resistant S. aureus (MRSA) (MIC = 1 mg/L) infections, and assumed 100%ƒT>MIC target, revealed that registered ceftaroline dosages are sufficient to achieve assumed PTA, except MRSA infection in patients with augmented renal clearance (ARC). Conclusions: Our successfully developed model allows flexible PK simulations of ceftaroline, including real-time changes in settings and even temporary or permanent cessation of CRRT. However, the results of our study warrant clinical validation and should be used with caution primarily due to the limited CRRT patient number included in the analysis.